Academic Writing Development of Master’s Thesis Pair Writers: Negotiating Writing Identities and Strategies - Wirenfeldt Jensen, Tine; Nordentoft, Helle Merete (Journal of Academic Writing, 2022)
This article provides insights into how writing a Master’s thesis in pairs affects students’ development and identity construction as academic writers (Burgess & Ivanič’s, 2010). Data consist of self-recorded dialogues between four pairs of Danish Master’s thesis writers at the start, middle and end of their thesis writing process. Data were coded thematically using grounded theory methods (Charmaz, 2006) and the resulting empirically grounded themes informed a discourse analysis of the material (Laclau & Mouffe, 2001). The findings suggest that those writing a Master’s thesis in pairs negotiate and assign largely fixed writing identities at an early stage that serve as a way of creating boundaries and building trust, allowing the students to write, provide feedback and revise text in shared documents. Each pair develops a set of writing strategies focused on setting and maintaining boundaries, thereby ensuring that the joint pair writer identity is not threatened. The article discusses how this strategy is embedded in a wider Master’s thesis discourse that draws heavily on concepts such as autonomy and independence and thus might not lend itself easily to the articulation of a joint identity as a writing pair.